Utilizing an Interactive Website for Elementary School Students to Learn about the Universe - Agustin, Ninik; Khanif, M.; Abdul Aziz Zein, Mochamad Taufiqurrochman; Rosad, Safiq; Martanti, Martanti; Azizaturrohmah, Nofriani; Prasetyo, Aldika Gagah; Zhalifunnas, Nicky Atikah (Universitas Teknokrat Indonesia, 2024)
Students in 6th-grade MI Ya BAKII Kesugihan 01 are not well informed about websites and using interactive websites to support their studies. One of the interactive websites is The Scale of The Universe. The website contains one of the materials at school that already being recognized by students, such as science material of the universe subchapter. This community services intended to improve the ability of 6th-grade students of MI Ya BAKII Kesugihan 01 to use interactive web technology and increase students' interest in studying through technology. This community service activity implemented through four phase which are the pre-implementation, the implementation, the monitoring and evaluation, and the post-service phase. The training conducted for the participants used the interactive website